2021
DOI: 10.3390/en14175541
|View full text |Cite
|
Sign up to set email alerts
|

HVAC Energy Saving Strategies for Public Buildings Based on Heat Pumps and Demand Controlled Ventilation

Abstract: The paper analyzes and compares the perspectives for reducing the energy consumption associated to the operation of Heating Ventilation and Air Conditioning system for climatic control of large-size non-residential buildings. Three different control strategies are considered comparing the use of boiler and heat pumps as heating systems and analyzing the use of demand-controlled ventilation, operating on the effective occupancy of the building. The control strategies are applied to two different educational bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The baseline and high-efficiency gas furnaces annually produced 4040 and 3402 kgCO 2 e of net heating emissions, respectively, and these values did not change when the emission factors varied (Figure ). When electric furnaces were used, home heating can be supplemented using a heat pump system to improve the efficiency of heat generated with electricity . The efficiency of a heat pump system was measured by the heating seasonal performance factor (HSPF) that represented the system’s heat input capacity per unit electricity (Btu/W-h).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline and high-efficiency gas furnaces annually produced 4040 and 3402 kgCO 2 e of net heating emissions, respectively, and these values did not change when the emission factors varied (Figure ). When electric furnaces were used, home heating can be supplemented using a heat pump system to improve the efficiency of heat generated with electricity . The efficiency of a heat pump system was measured by the heating seasonal performance factor (HSPF) that represented the system’s heat input capacity per unit electricity (Btu/W-h).…”
Section: Resultsmentioning
confidence: 99%
“…When electric furnaces were used, home heating can be supplemented using a heat pump system to improve the efficiency of heat generated with electricity. 83 The efficiency of a heat pump system was measured by the heating seasonal performance factor (HSPF) that represented the system's heat input capacity per unit electricity (Btu/W-h). Typical HSPF values for air source heat pumps in the CCMS database ranged from 8 to 12 Btu/W-h 84 kgCO 2 e at 0.428 kgCO 2 e/kWh, which was the U.S. national average for the baseline electric scenario (Figure 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another good example is cogeneration-CHPs which are currently producing around 11% of electricity and 15% of heat in Europe [43]. Moreover, combined cycle gas turbines (CCGT) [44], power to gas (P2G) equipment [45], heat pumps [46] and heating, ventilation and air-condition systems (HVACs) [47] are all good examples of increasing energy efficiency and flexibility by combining different energy elements. As the third possibility of creating stable and secure power system under the high RES penetration is the connecting different regions and market coupling.…”
Section: Flexibility In Generalmentioning
confidence: 99%
“…Data analytics applied to an office building have found that an alternative HVAC (Heating, Ventilation, and Air-Conditioning system) schedule that can reduce energy consumption by, on average, 2.7% [21]. A new controller based on occupancy prediction makes energy savings up to 75% possible [22]. Traylor et al [23], by means of EnergyPlus simulations, have found that savings up to 5-15% could be achieved by modulating indoor temperatures in cooling applications.…”
Section: Introductionmentioning
confidence: 99%